A critical discourse analysis of English farewell addresses - Nguyễn Thị Quỳnh Hoa; Ngô Thị Ngọc Anh (Tạp chí Khoa học và Công nghệ)
US Presidential speeches are considered among the most influential speeches not only in the US but also around the world. This article is aimed at identifying lexical and grammatical features in English Farewell Addresses by U.S. Presidents (EFAUPs) and revealing the messages embedded in these speeches. The framework of critical discourse analysis (CDA) proposed by Fairclough with a three-stage procedure combined with Halliday’s Functional Grammar was applied. The research data were four English farewell addresses made by the Presidents of the United States in the first two decades of the 21st century. The results reveal that there are seven typical lexical features and eight grammatical features, which serve to express Presidents’ power and ideologies. It is hoped that the research results can illustrate a way of conducting discourse analysis based on a combination of Fairclough’s model and Halliday’s theory, thereby bringing useful implications to the teaching and learning of CDA.